Analisis Strategi Pemasaran Jasa Pada Perusahaan Traveloka - Monika Claudia Sarita; Fadila Hardika Putri (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
In line with technological developments in the world today, many companies provide services through social media or websites. This strategy follows technological developments, namely using online services. The purpose of this research is to find out the strategies used by Traveloka in marketing its services in line with technological developments. The approach used is a qualitative approach with this research data using secondary data collection methods. This research data uses a secondary data collection method by conducting a literature study by reading the literature. The research results show that there is a physical form of marketing, namely product marketing and some in the form of service marketing. Service marketing is basically immaterial and intangible because the product cannot be seen or felt. Marketing via online media is used by Traveloka to understand the level of consumer satisfaction and trust in using the sales site. Traveloka is a service company that provides various services ranging from accommodation tickets, entertainment tickets, to hotel rentals. Traveloka moves through websites and applications by implementing Traveloka's own strategy using several marketing mix strategies, namely price, place, promotion, product and process.